Portfolio balance approach to asymmetries, structural breaks and financial crisis: Testing a model for Nigeria - Oluwasegun B. Adekoya (CBN Journal of Applied Statistics, 2020)
This study tests the Portfolio Balance Theory (PBT) for Nigeria for the period starting from September, 1997 to September, 2018. It extends the hypothesized linear inverse relationship between exchange rate and stock price to include asymmetries and structural breaks. It further examines the impact of the 2008 global financial crisis on the PBT to determine its stability after the crisis. The full sample results show that the PBT holds for Nigeria and asymmetries and structural breaks matter in the nexus between stock price and exchange rate. However, the impact of stock price on exchange rate diminished in the long-run with the advent of the 2008 global financial crisis, thus eroding the relative consistency of the PBT after the crisis. The sensitivity of the Nigerian exchange rate to stock price changes calls for the strengthening ofthe stock market performance through relevant policies including the enhancementof portfolio diversification and risk-hedging assets. The role of asymmetries shouldnot also be jettisoned in predicting exchange rate with stock prices to obtain accurate forecast results.
Keywords: F31; G11; 330; Asymmetries; exchange rate; global financial crisis; portfolio balance theory; stock price; structural breaks